Project Approach to the upbringing of children of elementary school age within the Сoncept of The New Ukrainian School (NUS) - Horkavchuk, O. (Problems of Engineer-Pedagogical Education, 2019)
The article is dedicated to the application of the project-oriented and problem-aimed training into the educational process and its qualitative influence on the development of children of elementary school age under the context of reforming the system of education of Ukraine. The paper analyzes the aim and main components of the New Ukrainian School concept which form the new generation of Ukrainians with modern competences and values; considers the structure of the State Standard of General Elementary Education; provides definitions of the terms “project activities” and “the New Ukrainian School”. The sources for the New Ukrainian School concept are reviewed along with the successful experience of the education system reforming in the leading countries with rapidly growing economies. The terms “a project”, “a project approach”, “project-based learning”, “problem-based learning”, “critical thinking” are analyzed in more detail. The paper presents the results of the comparative analysis of the project approach application into the systems of general elementary education in Ukraine and countries of the European Union